Repercussions of the diagnosis of fetus malformation under the light of Betty Neuman's theory - Cristiane Vanessa da Silva; Thais Cerqueira Carvalho; Dibulo Ferreira Abrão; Adriana Peixoto da Silva; Fernanda Rodrigues Chaves de Morais; Ivia Santos de Carvalho (Universidade Federal do Ceará, 2022)
Objective: to understand the repercussions of the fetus malformation diagnosis in the life of pregnant women, under the light of Betty Neuman's theory. Methods: qualitative study, based on Betty Neuman's theory. The semistructured interview included ten women pregnant with malformed fetuses hospitalized in a maternity hospital specialized in fetal risk. The thematic analysis technique was used, respecting all ethical aspects. Results: the way in which the malformation is communicated, the lack of empathy from professionals, the lack of information, being alone, fearing judgment, and feeling guilty led to emotional alterations and changes in the projects of the pregnant women. The family, specialized care, and religiosity contributed for the balance of the participants. Conclusion: Neuman's theory allowed us to recognize stressing factors that shook the lines of defense of the pregnant women, leading to fragilities which are overcome by specialized care and by a support network.